2009
DOI: 10.1016/j.jtcvs.2009.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myoblast sheet transplantation improves the diastolic function of a pressure-overloaded right heart

Abstract: Skeletal myoblast sheet transplantation improved the diastolic dysfunction and suppressed ventricular fibrosis with increased capillary density in a rat model of a pressure-overloaded right ventricle. This method might become a novel strategy for the myocardial regeneration of right ventricular failure in patients with congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…However, when stem/progenitor cells were injected into the myocardium or delivered through bloodstream to the heart, few cells were found engrafted within the host tissue few days after the administration [3][4][5][6][7]. For this reason, a number of biomaterials have been proposed as delivery systems to favor stem/progenitor cells engraftment into the cardiac muscle [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, when stem/progenitor cells were injected into the myocardium or delivered through bloodstream to the heart, few cells were found engrafted within the host tissue few days after the administration [3][4][5][6][7]. For this reason, a number of biomaterials have been proposed as delivery systems to favor stem/progenitor cells engraftment into the cardiac muscle [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Initial results from trials in human patients using autologous bone marrow cells have shown that improvement in cardiac function is not satisfactory and remuscularization mediated by donor cells within damaged myocardium is unlikely to be the basis for functional recovery. 7 Recently, emerging tissue engineering approaches, such as synthetic biomaterial cardiac patch, 10 hydrogel, 11,12 or cell sheet, [13][14][15][16][17][18][19][20] offer another pathway to achieve damaged myocardium recovery and may overcome the insufficiency of current treatments. 21 Studies suggest that a three-dimensional (3D) tissue culture environment is necessary for efficient CM survival, functioning myocardial tissue formation in vitro, functional integration, and sustained cardiac recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that cell sheet cardiac graft is relatively easily constructed and also scalable to the human patients. [13][14][15][16][17]19 Combination of proliferative CM and the cell sheet technology, such as layered cell sheet 18 or cell aggregate patch, 20 may enable us to test whether high CM proliferation activity is maintained in a larger-scale engineered cardiac graft. Further studies are necessary to determine whether the high CM proliferation and low CM apoptosis activities within EFCT are purely intrinsic properties of fetal type CMs.…”
mentioning
confidence: 99%
“…Two plant extracts improved right ventricular function in rat models of PAH that otherwise produces severe right ventricular failure [24 ,48 ]. A tissue-engineered skeletal myoblast sheet improved right ventricular diastolic function, fibrosis, and capillary density, also in a rat model of PAH [49 ]. Other unique initial studies have suggested a possible therapeutic role for cardiac resynchronization therapy in PAH via right ventricular pacing.…”
Section: Treatment Of Pressure Overloaded Right Ventricular Dysfunctionmentioning
confidence: 94%